Eksplorasi Etnomatemaika pada Rancangan Bangun Rumah Adat Ede Kampung Umbu Koba Sumba Barat Daya: Rumah adat - Lero, Oktavianus Wunu; Bili, Mardiyanto Ginto; Lede, Yulius Keremata (Indo-MathEdu Intellectuals Journal, 2026)
The purpose of this study was to determine the philosophical meaning and mathematical elements contained in the design of the Ede traditional house. This type of research is aqualitative research with an ethnographic approach, namely an empirical and theoretical approach that aims to obtain an in-depth description and analysis of culture based on intensive fieldwork. The subjects of this study were the historians of the Ede traditional house, namely Mrdominggus bulu, and Mr. oktavianus ngongo. Data collection techniques used are observation guidelines and interview guidelines. The mathematical element in the design of the Ede (Uma katoda) traditional house in Umbu Koba village contains geometric elements such as points, lines, and planes. In the Ede traditional house there are also various geometries, namely plane geometry and space geometry. The geometry of the plane includes triangles, trapezoids, and rectangles. While the geometry of space such as blocks and cubes. In the design of the Ede (Uma katoda) traditional house in the form of a stage, it contains the meaning and principle of balance in it. There are three levels such as the first level as a place for animals, the second level as a shelter for humans and the third level as a place to store food. The high meaning of minarets in the Ede traditional house of Umbu Koba village does not indicate social status but is directed at the Creator or a sign of human greatness and position to establish a relationship with God.